DEPOSISI FILM TIPIS FERROELEKTRIK DENGAN METODE PULSE LASER DEPOSITION DAN KARAKTERISASINYA - AWITDRUS
Deposition of Bao3Sr07TiO3 ferroelectric thin films on Pt/SiO 2/Si and Si substrate at temperature of 650 °C, 675 °C and 700 °C using pulse laser deposition method have been done. Preparation of Bao.3Sro,TiO3 ferroelectric target start from mixing of BaCO3, SrCO3 and TiO2 by solid state reaction, calcined at temperature of 1100 °C for 2 hours and sintering at temperature of 1350 °C for 4 hours. Ba03Sr07TiO3 ferroelectric thin films have been in-situ annealed at temperature of 700 °C for 30 minutes and followed by ex-situ annealing at temperature of 850 °C for 5 hours. Ba03Sr07TiO3 ferroelectric thin films were characterization using X-ray diffraction, scanning electron microscopy, hysteresis and capacitance-voltage measurement. X-ray diffraction characterization shows that the quality of Ba03Sr0.7TiO3 ferroelectric thin film improve significant by increasing the deposition temperature. This improvement indicated by XRD peak intensity, increasing on (200) crystal plane, arising of new peak and FWHM decreasing. Hysteresis and capacitancevoltage measurement shows maximum remanent polarization (Pr), coercive field (Ec), dielectric constant (a) and capacitance are 0, 806 jun/cm2, 137,909 kV/cm, 70 and 25,5 pF respectively of flme grown at deposition temperature of 700 °C.